Carbon nanomaterials and their impact on membrane separation applications. Issue 11 (6th October 2021) - Rogers, Reginald E.; Martin, Stephen M.
Abstract : Design, use, and recyclability of carbon nanomaterials in membranes provide new opportunities for advancing separation applications. Abstract : Carbon nanomaterials ( e.g. carbon nanotubes, graphene, fullerenes, etc. ) have captured the attention of researchers for the past several decades. Given their unique structure and properties, these nanomaterials have been shown to have high versatility in a variety of applications. In recent years many of these nanomaterials have been investigated for separation applications. One specific application where carbon nanomaterials have elicited a high level of interest is their use in membrane technology. Given the desire to develop new technologies for separation applications, such as water purification, advances in membrane technology are a high priority. This perspective focuses on carbon nanomaterials in membrane separations from bench to scale up as well as economic and environmental implications for a variety of applications.